Light availability determines susceptibility of reef building corals to ocean acidification - Suggett, DJ; Dong, LF; Lawson, T; Lawrenz, E; Torres, L; Smith, DJ (2013)
Elevated seawater pCO2, and in turn ocean acidification (OA), is now widely acknowledged to reduce calcification and growth of reef building corals. As with other environmental factors (e. g., temperature and nutrients), light availability fundamentally regulates calcification and is predicted to change for future reef environments alongside elevated pCO2 via altered physical processes (e. g., sea level rise and turbidity); however, any potential role of light in regulating the OA-induced reduction of calcification is still unknown. We employed a multifactorial growth experiment to determine how light intensity and pCO2 together modify calcification for model coral species from two key genera, Acropora horrida and Porites cylindrica, occupying similar ecological niches but with different physiologies. We show that elevated pCO2 (OA)-induced losses of calcification in the light (GL) but not darkness (GD) were greatest under low-light growth conditions, in particular for A. horrida. High-light growth conditions therefore dampened the impact of OA upon GL but not GD. Gross photosynthesis (PG) responded in a reciprocal manner to GL suggesting OA-relieved pCO2 limitation of PG under high-light growth conditions to effectively enhance GL. A multivariate analysis of past OA experiments was used to evaluate whether our test species responses were more widely applicable across their respective genera. Indeed, the light intensity for growth was identified as a significant factor influencing the OA-induced decline of calcification for species of Acropora but not Porites. Whereas low-light conditions can provide a refuge for hard corals from thermal and light stress, our study suggests that lower light availability will potentially increase the susceptibility of key coral species to OA. © 2012 Springer-Verlag Berlin Heidelberg.